2015
DOI: 10.1158/2326-6066.cir-14-0133
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression Correlates with Tumor-Infiltrating Lymphocytes and Response to Neoadjuvant Chemotherapy in Breast Cancer

Abstract: Programmed death 1 ligand 1 (PD-L1) is an immune regulatory molecule that limits antitumor immune activity. Targeting of PD-L1 and other immune checkpoint proteins has shown therapeutic activity in various tumor types. The expression of PD-L1 and its correlation with response to neoadjuvant chemotherapy in breast cancer has not been studied extensively. Our goal was to assess PD-L1 expression in a cohort of breast cancer patients treated with neoadjuvant chemotherapy. Pre-treatment biopsies from 105 breast can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
248
5
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(298 citation statements)
references
References 33 publications
24
248
5
10
Order By: Relevance
“…In 2014, 46 they showed that "PDL1 mRNA expression high" (57%) patients presented higher rates of pCR than "PDL1 mRNA expression low" (43%) patients (p < 0.001). Wimberley et al 47 showed that PDL1 protein levels in the epithelium and stroma were correlated with pCR only in hormone receptor-positive and HER2-amplified breast cancers. Denkert et al 44 demonstrated the importance of TIL and immune GE signatures for predicting pCR in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, 46 they showed that "PDL1 mRNA expression high" (57%) patients presented higher rates of pCR than "PDL1 mRNA expression low" (43%) patients (p < 0.001). Wimberley et al 47 showed that PDL1 protein levels in the epithelium and stroma were correlated with pCR only in hormone receptor-positive and HER2-amplified breast cancers. Denkert et al 44 demonstrated the importance of TIL and immune GE signatures for predicting pCR in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to CD8, PD-L1 expression has been ascribed ambivalent prognostic significance. It has been correlated with decreased survival in esophageal, gastric, ovarian, pancreatic, and renal cell carcinomas (20)(21)(22)(23)(24)(25), and has been associated with an improved survival in patients with Merkel cell (26), breast (27), and cervical carcinomas (28). Conflicting reports also exist regarding its significance within the same tumor type (e.g., melanoma and NSCLC) (6,(29)(30)(31).…”
mentioning
confidence: 99%
“…In another neo-adjuvant study of triple-negative patients who received chemotherapy with or without the anti-EGFR antibody panitumumab, patients with higher CD8+ TILs (defined in this study as a TILs count >118) had an 84% pCR rate as compared to 10% in patients with low TILs (37). In addition, a positive correlation of TILs with PD-L1 expression in cancer cells and stroma and with complete pathologic response (pCR) following neo-adjuvant chemotherapy was shown in another study (38). Specific sub-sets predicting for a good pCR rate included CD8+ infiltrates and FOXP3+ but persistence of FOXP3+ TILs after neo-adjuvant treatment was associated with an inferior complete pathologic response rate (34).…”
Section: Tils As a Prognostic Marker And Possible Predictive Marker Omentioning
confidence: 50%